2008
DOI: 10.1038/cdd.2008.166
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction triggered by loss of HtrA2 results in the activation of a brain-specific transcriptional stress response

Abstract: Cellular stress responses can be activated following functional defects in organelles such as mitochondria and the endoplasmic reticulum. Mitochondrial dysfunction caused by loss of the serine protease HtrA2 leads to a progressive movement disorder in mice and has been linked to parkinsonian neurodegeneration in humans. Here, we demonstrate that loss of HtrA2 results in transcriptional upregulation of nuclear genes characteristic of the integrated stress response, including the transcription factor CHOP, selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
151
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(159 citation statements)
references
References 37 publications
(57 reference statements)
6
151
2
Order By: Relevance
“…In lymphocytes, the presence of HtrA2 prevents accumulation of activated Bax in the mitochondrial outermembrane, which would initiate cytochrome c release and cell death. 12 Moisoi et al 30 showed that HtrA2 is necessary for preventing accumulation of unfolded protein and oxidative stress in mitochondria. A recent study by Li et al 31 reported that HtrA2 is responsible for the maintenance of constitutive autophagy, which can eliminate damaged mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…In lymphocytes, the presence of HtrA2 prevents accumulation of activated Bax in the mitochondrial outermembrane, which would initiate cytochrome c release and cell death. 12 Moisoi et al 30 showed that HtrA2 is necessary for preventing accumulation of unfolded protein and oxidative stress in mitochondria. A recent study by Li et al 31 reported that HtrA2 is responsible for the maintenance of constitutive autophagy, which can eliminate damaged mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…30 Omi is a key component needed to maintain mitochondrial integrity and the function of the respiratory chain, and loss of Omi produces a large number of damaged mitochondria. 10,29 We report here that Omi is responsible for the maintenance of constitutive autophagy (Figure 2). The autophagy system is a conserved pathway that eliminates damaged mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…28 Recently, an important finding revealed that the loss of Omi activates the PERK branch of the UPR, with transcriptional upregulation of CHOP and modulation of a number of other genes leading to neuronal cell death. 29 It is therefore possible that the upregulation of Omi and resulting activation of autophagy in response to stress are protective reactions, and the loss of this protective effect could result in sustained activation of the UPR. The upregulation of Omi by ER stress is similar to that observed for other prosurvival stress response proteins such as Grp78, which is also upregulated in response to ER stress; its knockdown also spontaneously activates UPR and upregulates CHOP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, increased ROS production was previously reported in thymocytes and MEFs from HtrA2-deficient mice. 24 ROS could damage the respiratory complexes and other mitochondrial proteins including PolgA, resulting in decreased respiratory chain activity, and increased mutation and deletions of mtDNA. Eventually, these deleterious effects can cause mitochondrial dysfunction, which triggers mitophagy to clear the defective mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…22 HtrA2 (also known as Omi) is an ATP-independent serine protease structurally and functionally related to the bacterial quality control proteases DegP and DegS. 23 HtrA2 resides in the intermembrane space of the mitochondrion, and its loss leads to accumulation of unfolded proteins in the mitochondria, oxidative stress, and defective mitochondrial respiration, 24 suggesting that, like its bacterial counterparts, HtrA2 functions as a quality control protease. Mice lacking HtrA2 protease activity as a result of missense mutation (mnd2 mice) or targeted deletion (HtrA2 knockout mice) of the HtrA2 (Prss25) gene exhibit early onset neurodegeneration and motor abnormalities similar to Parkinson's disease, and die between postnatal day (dP) 30 and dP40.…”
mentioning
confidence: 99%